2009
DOI: 10.1146/annurev.cellbio.24.110707.175411
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Organ Formation: Insights From theC. elegansForegut

Abstract: The digestive tracts of many animals are epithelial tubes with specialized compartments to break down food, remove wastes, combat infection, and signal nutrient availability. C. elegans possesses a linear, epithelial gut tube with foregut, midgut, and hindgut sections. The simple anatomy belies the developmental complexity that is involved in forming the gut from a pool of heterogeneous precursor cells. Here, I focus on the processes that specify cell fates and control morphogenesis within the embryonic foregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 239 publications
(371 reference statements)
5
77
1
Order By: Relevance
“…Early morphogenesis of the pharynx occurs in several phases (Sulston et al 1983;Portereiko and Mango 2001;Mango 2009). In the first phase, the lumen of the pharynx elongates through polarization of the anterior pharyngeal cells ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early morphogenesis of the pharynx occurs in several phases (Sulston et al 1983;Portereiko and Mango 2001;Mango 2009). In the first phase, the lumen of the pharynx elongates through polarization of the anterior pharyngeal cells ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…At this point, the nuclei of the arcade cells have been displaced posteriorly but remain attached to the arcade ring through cytoplasmic bridges ( Figure 3A, bottom). Genetic analyses have identified Pun mutants that fail at different times during buccal morphogenesis (Portereiko and Mango 2001;Mango 2009). To check for polarization of the anterior pharyngeal cells in our mutants, we visualized adherens junctions through staining of embryos with an a-MH27 antibody, which recognizes AJM-1 (Figure 3, B-G).…”
Section: Resultsmentioning
confidence: 99%
“…Because the transcription factor PHA-4 (FoxA) is thought to be required for most, if not all, aspects of pharyngeal-specific differentiation (reviewed by Mango, 2009), we examined formation of the double plate in pha-4(q490) null mutants. We found that the timing and patterning of the early PPC divisions in pha-4(q490) embryos appeared similar to wild type (data not shown) and that all of the PPCs ingressed (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…In Caenorhabditis elegans, the foregut, which includes the buccal cavity, pharynx, and intestinal valve cells, has proven to be a powerful model for studies of the molecular mechanisms controlling organogenesis (Mango 2007(Mango , 2009. Although containing only 95 nuclei in the adult, the foregut is composed of seven distinct but functionally integrated cell types, which arise from diverse embryonic lineages (Albertson and Thomson 1976;Sulston et al 1983).…”
mentioning
confidence: 99%